sqrt(9v+2)=sqrt(6v+11)

Simple and best practice solution for sqrt(9v+2)=sqrt(6v+11) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for sqrt(9v+2)=sqrt(6v+11) equation:


Simplifying
sqrt(9v + 2) = sqrt(6v + 11)

Reorder the terms:
qrst(2 + 9v) = sqrt(6v + 11)
(2 * qrst + 9v * qrst) = sqrt(6v + 11)
(2qrst + 9qrstv) = sqrt(6v + 11)

Reorder the terms:
2qrst + 9qrstv = qrst(11 + 6v)
2qrst + 9qrstv = (11 * qrst + 6v * qrst)
2qrst + 9qrstv = (11qrst + 6qrstv)

Solving
2qrst + 9qrstv = 11qrst + 6qrstv

Solving for variable 'q'.

Move all terms containing q to the left, all other terms to the right.

Add '-11qrst' to each side of the equation.
2qrst + -11qrst + 9qrstv = 11qrst + -11qrst + 6qrstv

Combine like terms: 2qrst + -11qrst = -9qrst
-9qrst + 9qrstv = 11qrst + -11qrst + 6qrstv

Combine like terms: 11qrst + -11qrst = 0
-9qrst + 9qrstv = 0 + 6qrstv
-9qrst + 9qrstv = 6qrstv

Add '-6qrstv' to each side of the equation.
-9qrst + 9qrstv + -6qrstv = 6qrstv + -6qrstv

Combine like terms: 9qrstv + -6qrstv = 3qrstv
-9qrst + 3qrstv = 6qrstv + -6qrstv

Combine like terms: 6qrstv + -6qrstv = 0
-9qrst + 3qrstv = 0

Factor out the Greatest Common Factor (GCF), '3qrst'.
3qrst(-3 + v) = 0

Ignore the factor 3.

Subproblem 1

Set the factor 'qrst' equal to zero and attempt to solve: Simplifying qrst = 0 Solving qrst = 0 Move all terms containing q to the left, all other terms to the right. Simplifying qrst = 0 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.

Subproblem 2

Set the factor '(-3 + v)' equal to zero and attempt to solve: Simplifying -3 + v = 0 Solving -3 + v = 0 Move all terms containing q to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + v = 0 + 3 Combine like terms: -3 + 3 = 0 0 + v = 0 + 3 v = 0 + 3 Combine like terms: 0 + 3 = 3 v = 3 Add '-1v' to each side of the equation. v + -1v = 3 + -1v Combine like terms: v + -1v = 0 0 = 3 + -1v Simplifying 0 = 3 + -1v The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.

See similar equations:

| x^2-11x-2/3x-15 | | -4w=7 | | 2(-7k+16k)= | | 2x-1+8x+8= | | y=160(x)+45 | | 2500=3.14r^2 | | 20-1q=17 | | 60y-84= | | 2cosx=1.7 | | 4x=3y-x | | -12+5u=48 | | 8+r+2=-9 | | .33x+5=-22 | | 2000=3.14r^2 | | 9x-6/21x-14 | | -12+5u= | | R+8.5=21 | | 12e-40+45=3e+5 | | 4-3(-5)= | | 7n-11=3n+5 | | 10x-40/5 | | -2+6(-7)= | | y=400(x)+15 | | 7n-11=3n-5 | | 5(-3)-5= | | C+1=2c-6 | | -4-5(7)= | | 42x+1=1024 | | 13=52/W | | 4x^4-6x^2=0 | | 2-5(-5)= | | Y=-2x(X+4) |

Equations solver categories